A model of Austrian economics - Hagedorn, Hendrik (Springer, 2015)
After the most recent financial crisis it has become clear that there exists a crisis also in economics as a science. The prevailing paradigms have failed to anticipate and to understand the financial crisis. New approaches are therefore needed. Of particular interest should be approaches that combine insights from those parts of economics that are largely neglected by the mainstream. Hendrik Hagedorn presents a model that synthesizes elements of Austrian, post-Keynesian, and evolutionary economics. Thus, an economic paradigm is developed that challenges neoclassical economics as a whole.